2022
DOI: 10.3390/pathogens11030372
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inflammatory and Regulatory Cytokines IL-1α-, IL-4-, IL-6-, IL-12-, IL-13-, IL-17A-, TNF-α-, and IFN-γ-Producing Cells in the Milk of Dairy Cows with Subclinical and Clinical Mastitis

Abstract: In naturally occurring bovine mastitis, effects of infection depend on the host inflammatory response, including the effects of secreted cytokines. Knowledge about the inflammatory and regulatory cytokines in milk cells of free-stall barn dairy cows and in naturally occurring mastitis is lacking as most studies focus on induced mastitis. Hereby, the aim of the study was to determine inflammatory and regulatory cytokines in the milk of dairy cows with subclinical and clinical mastitis. The following examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 100 publications
0
23
0
3
Order By: Relevance
“…In ruminants, lactoferrin has been shown to inhibit the multiplication of E. coli by binding to iron ions, making them unavailable for bacterial growth ( Rybarczyk et al, 2017 ; Kieckens et al, 2018 ). Additionally, cytokines including interleukins (IL), colony-stimulating factor (CSF), interferon (IFN), and tumor necrosis factor (TNF) are crucial in the mammary gland innate defense ( Bhattarai et al, 2018 ; Vitenberga-verza et al, 2022 ). Cytokines are responsible for local signs of inflammation such as swelling, redness, pain, and systemic symptoms such as fever, tachycardia, increased respiratory rate, anorexia, and depression ( Sordillo et al, 1997 ; Thompson-Crispi et al, 2014 ).…”
Section: Host Immune Response To Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…In ruminants, lactoferrin has been shown to inhibit the multiplication of E. coli by binding to iron ions, making them unavailable for bacterial growth ( Rybarczyk et al, 2017 ; Kieckens et al, 2018 ). Additionally, cytokines including interleukins (IL), colony-stimulating factor (CSF), interferon (IFN), and tumor necrosis factor (TNF) are crucial in the mammary gland innate defense ( Bhattarai et al, 2018 ; Vitenberga-verza et al, 2022 ). Cytokines are responsible for local signs of inflammation such as swelling, redness, pain, and systemic symptoms such as fever, tachycardia, increased respiratory rate, anorexia, and depression ( Sordillo et al, 1997 ; Thompson-Crispi et al, 2014 ).…”
Section: Host Immune Response To Escherichia Colimentioning
confidence: 99%
“…(Zhang et al, 2017), MPEC have undergone evolutionary adaptations (e.g., acquisition of VFs) that improve its colonization of the unique environmental niches found within the mammary gland (Shpigel et al, 2008). These niches include competing microbes, soluble and cellular antimicrobials in milk, e.g., lactoferrin and lactoperoxidase (Kawai et al, 2015;Koshiishi et al, 2017), and the innate response elicited by immune cells (Wellnitz and Bruckmaier, 2012). Consequently, E. coli with specific VFs selected within the mammary gland are better suited to cause bovine mastitis (Blum et al, 2015;Richards et al, 2015;Goldstone et al, 2016;Roussel et al, 2017;Sun et al, 2021;Zhou et al, 2021).…”
Section: The Dilemma Of Mammary Pathogenic Escherichia Coli As a New ...mentioning
confidence: 99%
“…Seven non-synonymous SNVs were detected in four mastitis associated genes (Table 6). Vitenberga-Verza et al (46) showed that immunoreactivity was more pronounced for IL-4 in mastitis cases. We identified a non-synonymous mutation in the IL4 gene that coding for IL4.…”
Section: Resultsmentioning
confidence: 98%
“…Among them, TNF-α and IL-1 are essential for mediating the recruitment of leukocytes to the site of the inflammation [ 34 ]. TNF-α and IL-6 are immunoreactive in cases of mastitis, while IL-1α of the IL-1 family is more capable of driving the corresponding inflammatory response [ 35 ]. These pro-inflammatory cytokines can promote the proliferation of S. aureus within the bovine mammary epithelium [ 36 ].…”
Section: Discussionmentioning
confidence: 99%